Risks and benefits of dolutegravir-based antiretroviral drug regimens in sub-Saharan Africa: a modelling study. Issue 2 (February 2019) - Phillips, Andrew N; Venter, Francois; Havlir, Diane; Pozniak, Anton; Kuritzkes, Daniel; Wensing, Annemarie; Lundgren, Jens D; De Luca, Andrea; Pillay, Deenan; Mellors, John; Cambiano, Valentina; Bansi-Matharu, Loveleen; et al.
Summary: Background: The integrase inhibitor dolutegravir could have a major role in future antiretroviral therapy (ART) regimens in sub-Saharan Africa because of its high potency and barrier to resistance, good tolerability, and low cost, but there is uncertainty over appropriate policies for use relating to the potential for drug resistance spread and a possible increased risk of neural tube defects in infants if used in women at the time of conception. We used an existing individual-based model of HIV transmission, progression, and the effect of ART with the aim of informing policy makers on approaches to the use of dolutegravir that are likely to lead to the highest population health gains. Methods: We used an existing individual-based model of HIV transmission and progression in adults, which takes into account the effects of drug resistance and differential drug potency in determining viral suppression and clinical outcomes to compare predicted outcomes of alternative ART regimen policies. We calculated disability adjusted life-years (DALYs) for each policy, assuming that a woman having a child with a neural tube defect incurs an extra DALY per year for the remainder of the time horizon and accounting for mother-to-child transmission. We used a 20 year time horizon, a 3% discount rate, and a cost-effectiveness threshold of US500 per DALY averted. Findings: The greatest number of DALYs is predicted to be averted with use of a policy in which tenofovir, lamivudine, and dolutegravir is used in all people on ART, including switching to tenofovir, lamivudine, and dolutegravir in those currently on ART, regardless of current viral load suppression and intention to have (more) children. This result was consistent in several sensitivity analyses. We predict that this policy would be cost-saving. Interpretation: Using a standard DALY framework to compare health outcomes from a public health perspective, the benefits of transition to tenofovir, lamivudine, and dolutegravir for all substantially outweighed the risks. Funding: Bill & Melinda Gates Foundation.